Pengaruh Jumlah Lapisan dan Spasi Perkuatan Geosintetik terhadap Kuat Dukung dan Penurunan Tanah Lempung Lunak - Anita Widianti (Universitas Muhammadiyah Yogyakarta, 2012)
One of the ways to improve the mechanical characteristics of soft soil is to provide soil reinforcement which is a geosynthetic sheet overlaid on the soft soil. Previous studies show that the installation of geosynthetic layers in soft soil proved to increase the bearing capacity and reduce the settlement. Theoretically, if more layers of reinforcement are given, the support will be stronger, while the soil of settlement will be reduced even greater. In this study, the influence of the number of layers and vertical distance between geosynthetic layers on the magnitude of bearing capacity, and the settlement in base soil will be assessed. The primary research is a load test on each clay included in model boxes of 120 cm x 120 cm x 100 cm size. Water was added to the soil to achieve the liquid limit conditions, then the soil was strengthened by inserting 60 x 60cm2 HRX200 woven geotextile layers whose tensile strength is 20 kN/m2 with various distances and number of layers among different boxes. The bottom of loading foundation on the top side of the samples is square whose side (B) is of 10 cm. The loading process were done until the soil collapse indicated by visual observation or by the condition of no increase of the load magnitude causing settlement. The results showed that 1 layer, 2 layers and 3 layers geosynthetic correspond to the bearing capacity increase of 60.57%, 213.00% and 402.64%, respectively, and experienced a reduction in soil settlement by 40%, 60% and 70%, respectively, compared to that without any reinforcement. Geosynthetic being placed at a distance of 0.4 B and 0.6 B gives the greatest bearing capacity increase, in the amount of 402.64%. Geosynthetic mounted on distance more than 0.6 B resulted in bearing capacity increase of diminishing percentages.